'I'll always find a perfectly justified reason for not doing it': challenges for disability sport and physical activity in the United Kingdom - Ives, Ben; Clayton, Ben; Brittain, Ian; Mackintosh, Chris (Sport in society, 2021)
This study aimed to provide insight into the experiences of and attitudes to sport and physical activity for disabled people. Data were generated through semi-structured interviews with eight facilitators and focus groups with 24 members across three disability support organisations. Using ableism as the primary sensitising concept, our iterative analysis revealed that although all facilitators and disabled people were aware of the physical and mental wellbeing benefits of sport and physical activity, only 2 of the 24 disabled participants met the UK Government guidelines for physical activity. Findings showed that participation was hampered by a number of external and internal barriers, including the cost of transport and activities, ineffective modes of communication and advertisement, preconceived images of sport as competitive and judgemental, and anxieties about sporting abilities. Importantly, this study highlighted that many of these barriers were a pretext for a lack of enjoyment, and makes suggestions for future practice.